RLM1, Encoding an R2R3 MYB Transcription Factor, Regulates the Development of Secondary Cell Wall in Rice - Chen, Zhenhua; Teng, Shouzhen; Liu, Di; Chang, Yuan; Zhang, Liying; Cui, Xuean; Wu, Jinxia; Ai, Pengfei; Sun, Xuehui; Lu, Tiegang; Zhang, Zhiguo (Frontiers in Plant Science, 2022)
Leaf morphology is an important component of rice ideal plant type. To date, many regulatory genes influencing leaf morphology in rice have been cloned, and their underlying molecular regulatory mechanism has been preliminarily clarified. However, the fine regulation relationship of leaf morphogenesis and plant type remains largely elusive.In this study, a rolling-leaf mutant, named rlm1, was obtained and controlled by a pair of dominant nuclear genes. Cytological observations revealed that the rlm1 was mainly caused by abnormal deposition of secondary cell walls. Molecular evidence showed ectopic expression of a MYB-type transcription factor LOC_Os05g46610 was responsible for the phenotype of rlm1. A series of experiments, including the transcription factor-centered technology, DNA-binding assay and electrophoretic mobility shift assay, verified that RLM1 can bind to the promoter of OsCAD2, a key gene responsible for lignin biosynthesis in rice. An interacting partner of RLM1, OsMAPK10, was identified. Multiple biochemical assays confirmed that OsMAPK10 interacted with RLM1. OsMAPK10 positively regulated the lignin content in the leaves and stems of rice. Moreover, OsMAPK10 contributes to RLM1 activation of downstream target genes. In particular, RLM1 is exclusively expressed in the stems at the mature plant stage. The yield of RLM1 knockdown lines increased by over 11% without other adverse agricultural trait penalties, indicating great practical application value. A MAPK-MYB-OsCAD2 genetic regulatory network controlling SCW was proposed, providing a theoretical significance and practical value for shaping the ideal plant type and improving rice yield.